Resilience of Indonesian Migrant Workers' Children in Malaysia - Indahyati, Laila Nur; Setiyowati, Ninik (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
Children of Indonesian Migrant Workers in Malaysia face various limitations and challenges, such as restricted access to education and healthcare. This study aims to explore the resilience of children of Indonesian migrant workers in Malaysia using a qualitative approach and a case study method. The selection of informants was conducted through purposive sampling based on specific criteria, with a total of four informants. Data collection was carried out through observation, interviews, and documentation, followed by thematic analysis. To ensure data validity, source triangulation was employed. The findings reveal that the resilience of the four informants is derived from three main sources: I Have, I Am, and I Can. ‘’I Have’’ reflects the support received from family and friends, the presence of role models, established rules, and encouragement to become independent. ‘’I Am’’ reflects a sense of pride in oneself, feeling liked by others, possessing empathy and care for others, taking responsibility and accepting the consequences of one's actions, as well as having hope and confidence in the future. Meanwhile, ‘’I Can’’ reflects an individual's ability to communicate, manage feelings and emotions, and control impulses when facing problems.